2017
DOI: 10.1177/1759720x16687480
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and bone health: latest evidence and clinical implications

Abstract: As the prevalence of diabetes is increasing worldwide, research on some of the lesser-known effects, including impaired bone health, are gaining a lot of attention. The two most common forms of diabetes are type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM). These two differ in their physiology, with T1DM stemming from an inability to produce insulin, and T2DM involving an insufficient response to the insulin that is produced. This review aims to highlight the most current information regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 53 publications
2
53
0
13
Order By: Relevance
“…In addition to the altered systemic cytokine profile, the overexpression of hTNFα resulted in alterations in vertebral bone structure including cortical and trabecular thinning. There is a well‐established link between systemic inflammatory conditions and reduced bone mass for both smoking and diabetes . The state of the neighboring vertebral bone inflammation is pertinent to the discussion of degenerative disc disease: bone marrow inflammation with Modic changes, is highly correlated with painful disc degeneration .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the altered systemic cytokine profile, the overexpression of hTNFα resulted in alterations in vertebral bone structure including cortical and trabecular thinning. There is a well‐established link between systemic inflammatory conditions and reduced bone mass for both smoking and diabetes . The state of the neighboring vertebral bone inflammation is pertinent to the discussion of degenerative disc disease: bone marrow inflammation with Modic changes, is highly correlated with painful disc degeneration .…”
Section: Discussionmentioning
confidence: 99%
“…There is a well-established link between systemic inflammatory conditions and reduced bone mass for both smoking and diabetes. (38,39) The state of the neighboring vertebral bone inflammation is pertinent to the discussion of degenerative disc disease: bone marrow inflammation with Modic changes, is highly correlated with painful disc degeneration. (40,41) However, despite vertebral bone inflammation there were no corresponding changes in disc health.…”
Section: Discussionmentioning
confidence: 99%
“…These abnormalities might affect bone metabolism indexes by different mechanisms. 24 This study showed that FN BMD (0.83±0.13), LS BMD (1.03±0.18) and BMC (1.92±4.16) in T2DM group were lower than those of FN BMD (0.91±0.13), LS BMD (1.15±0.16), and BMC (2.12±4.29) in NGT group. And the BMC was also lower in T2DM group than pre-DM group (2.28±4.15).…”
Section: Discussionmentioning
confidence: 55%
“…While none of the patients in this study were reported as having clinical signs of metallosis or metal hypersensitivity, factors such as BMI, drug status, levels of physical activity and underlying comorbidities were not taken into account. Conditions including diabetes mellitus [39], a history of smoking [40] and obesity [41] have all been shown to affect bone health, and thus could potentially contribute to the changes observed. A larger cohort of patients with sufficient statistical power to allow multivariate analysis of all potentially contributing factors would help elucidate the influence of gender on the possible mechanisms of bone loss.…”
Section: Discussionmentioning
confidence: 99%